Cambrian--Ordovician Boundary Age and Duration of the Lowest Ordovician Tremadoc Series Based on U-Pb Zircon Dates from Avalonian Wales - E. Landing; Bowring, S. A.; Davidek, K. L.; Rushton, A.; Fortey, R. A.; Wimbledon, W. A. P. (Geological Magazine, 2000)
Two thin volcaniclastic sandstone beds in the Bryn-llin-fawr road section in North Wales overlie an apparent sequence boundary within the uppermost Cambrian Acerocare Zone and are overlain by lowest Ordovician (lower Tremadoc) Rhabdinopora faunas. U–Pb geochronology of zircons from these sandstones yields a maximum Cambrian–Ordovician boundary age of 489±0.6 Ma. This age indicates both that the Tremadoc Series (lowest Ordovician) may be shorter in duration than was previously thought and that the duration of the Middle and Late Cambrian (c. 22 Ma) was much less than that of the Early Cambrian (c. 33 Ma). Cambrian trilobite zones locally had an average duration as short as 1 Ma.
Keywords: Cambrian–Ordovician boundary; North Wales; trilobites; volcaniclastic sandstone